Being a Good Neighbor: Can Students Come to Value Homosexual Persons? - Bassett, Rodney L. (Journal of psychology and theology, 2005)
Attitudes toward gay/lesbian persons and behavior were initially assessed among Christian college students. Students with either uniformly positive or negative attitudes toward homosexual persons and behavior were then exposed to psychological and spiritual interventions designed to help them see more clearly the value of homosexual persons. Attitudes toward homosexual persons and behavior were then reassessed immediately after the intervention and one month later. Generally, the intervention improved attitudes toward homosexual persons. The picture for attitudes toward homosexual behavior was more complicated. With students who were uniformly rejecting, the intervention made their attitudes toward homosexual behavior less rejecting. However, with students who were uniformly accepting, the intervention diminished their acceptance of gay/lesbian behavior.